A comparison between the responsiveness of selected physiological and subjective mental workload indicators during real-world driving scenarios - Schmidtke, Nadia-Jasmine (Rhodes University, Faculty of Science, Department of Human Kinetics and Ergonomics, 2020)
Sub-optimal levels of mental workload in automobile drivers is a risk factor for road accidents. However, mental workload as a construct cannot be directly measured. Common indicators of mental workload include heart rate frequency and variability, eye motion and subjective rating tools. Namely, the National Aeronautics and Space Administration Task Load Index (NASA-TLX), its modified, unweighted version called the Raw-TLX, and the Rating Scale of Mental Effort (RSME). Comparisons between the suitability and responsiveness of these mental workload indicators have been almost exclusively examined in driving simulators. However, real-world driving research is important as even high-fidelity simulators cannot capture the complexity of driving scenarios. Hence, this research aimed to compare the suitability and responsiveness of these mental workload indicators in response to real-world driving scenarios. Six participants drove along a set route for an hour while wearing a heart rate monitor and eye tracker. A dashcam was used to capture footage of the different driving scenarios encountered. The set route comprised of driving through the industrial, residential, provincial main road and Rhodes University campus areas. RSME scores were taken during brief stops after driving though each zone. The NASA-TLX questionnaire was administered on completion of the drive and analysed later as the modified Raw-TLX version. The data collected in response to the encountered driving scenarios were sorted into three meta-groupings. (1) Data was segmented according to the different areas that participants drove through. This was termed Area Events and were long duration scenarios of between five and thirty minutes. These driving scenarios were further segmented into two meta-groups with short duration driving scenarios (< 90 seconds). (2) The Common Events meta-group consisted of driving scenarios that were encountered by all participants. These were scenarios were anticipated by drivers. (3) The All Events meta-group was grouped according to all the driving scenarios that were encountered by participants. It consisted of both anticipated and unanticipated driving scenarios of short durations. Data were further analysed using a method of systematically selecting a threshold value for each mental workload indicator. Responses to driving scenarios which surpassed the threshold were considered indicative of an increase in mental workload. The total frequency of higher mental workload events was used as a determiner responsiveness (or 'sensitivity') for each mental workload indicator. Mental workload indicators were evaluated for their responsiveness and suitability for assessing mental workload. Results found blink frequency to be a responsive mental workload indicator for all categories of driving scenarios. Blink frequency and duration were the most responsive short duration mental workload indicators. Furthermore, the indicators were able to distinguish between higher and lower mental workload driving scenarios. However, blink parameters are also sensitive to driver fatigue and drowsiness. Further research on distinguishing mental workload from that of fatigue in response to real-world driving was recommended. Pupil diameter, fixation duration, saccade saccade duration and saccade amplitude were found to be responsive short duration mental workload indicators. However, these measures were not determined to be suitable for real-world driving applications. Pupil diameter was confounded by changing illumination levels. Fixation and saccade responses were confounded by the driving task itself as gaze could not be accounted for. For long duration driving scenarios heart rate frequency, heart rate variability: high-frequency power, blink frequency and RSME were found to be responsive and suitable MWL indicators. The Raw-TLX results could not be assessed for responsiveness as it was administered once. However, it was confirmed as a suitable cumulative mental workload indicator in the application of real-world driving. The moderate levels of workload reported by participants agreed with the experimental protocol that prevented inducing sub-optimal mental workload. Blink frequency shows promise as a responsive and suitable mental workload indicator for different types of driving scenarios. More research is needed regarding the assessment of mental workload during short durations using blink frequency and blink duration. For driving durations between five and thirty minutes long, further research into heart rate frequency, heart rate variability: high frequency power, and the RSME was recommended.
Keywords: Automobile driving -- Physiological aspects; Automobile driving -- Psychological aspects; Automobile drivers -- Health and hygiene; Mental fatigue; Mental work -- Case studies